21st century skills in the United States: a late, partial and silent reform. Issue 1 (2nd January 2021) - Anderson-Levitt, Kathryn
ABSTRACT: This article examines the history of US movements for competencies, often called 'twenty-first century skills', in international context. Ironically, US actors were a source of early ideas about competencies but 'late' adopters of a competency-added reform—a partial and silent policy incorporated within the Common Core State Standards of 2010. The US case might appear to support a realist theory that the country independently invented the same solution to the same problem addressed by other countries' competency-based reforms. However, this article shows that some US actors actually invited international influence, supporting the theory that the common problem was actually a social construction. In addition, soft power exercised by technology corporations partly explains how the solution of a competency-added curriculum was finally adopted by most US states.